RANCANG BANGUN E-COMMERCE PADA PT. FAJAR SURYA WISESA, CIBITUNG - Sukardi dan Indra Harjanto (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTPT. Fajar Surya Wisesa ( PT. FASW) is a manufacturing company producing paper for packaging material.  About 30% of its products is exported while the rest is for domestic market. PT FASW intends to increase its export share to anticipate the free trade era. To achieve this objective, PT FASW needs to adopt a new marketing strategy to support product promotion. One of the marketing strategy alternatives that PT FASW looks for is e-commerce so that it can put its products information anytime, anywhere by utilizing website technology.  By developing e-commerce, PT FASW expects to be able to improve its company image at international market as well as to promote all of its products widely at low operational cost. The objectives of this research are (1) to design e-commerce system, and (2) to develop e-commerce software which can assist PT. FASW to market its products through internet. The developed e-commerce system includes, among others, registration of new customer, on-line order, payment method, detection of order status, information of payment status and invoice notification.Key words : e-commerce, packaging material, PT. FASW